Deflecting lithium dendritic cracks in multi-layered solid electrolytes - Hu, B; Zhang, S; Ning, Z; Spencer-Jolly, D; Melvin, DLR; Gao, X; Perera, J; Pu, SD; Rees, GJ; Wang, L; Yang, L; Gao, H; et al. (Cell Press, 2024)
Charging current densities of solid-state batteries with lithium metal anodes and ceramic electrolytes are severely limited due to lithium dendrites that penetrate the electrolyte leading to a short circuit. We show that dendrite growth can be inhibited by different crack deflection mechanisms when multi-layered solid electrolytes, such as Li6PS5Cl/Li3ScCl6/Li6PS5Cl and Li6PS5Cl/Li10GeP2S12/Li6PS5Cl, are employed but not when the inner layer is Li3PS4. X-ray tomographic imaging shows crack deflection along mechanically weak interfaces between solid electrolytes as a result of local mismatches in elastic moduli. Cracks are also deflected laterally within Li3ScCl6, which contains preferentially oriented particles. Deflection occurs without lithium being present. In cases where the inner layers react with lithium, the resulting decomposition products can fill and block crack propagation. All three mechanisms are effective at low stack pressures. Operating at 2.5 MPa, multi-layered solid electrolytes Li6PS5Cl/Li3ScCl6/Li6PS5Cl and Li6PS5Cl/Li10GeP2S12/Li6PS5Cl can achieve lithium plating at current densities exceeding 15 mA cm–2.